2011
DOI: 10.1590/s1516-31802011000300007
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for wound healing among diabetic patients infected with Staphylococcus aureus: a systematic review

Abstract: CONTEXT AND OBJECTIVE: Staphylococcus aureus is the most frequent agent isolated in diabetic foot infections and may be associated with changes to wound healing times. The aim of this study was to perform a systematic review of the literature, including studies that assessed the efficacy of any clinical or surgical intervention, as well as oral or topical therapy for diabetic ulcers infected with S. aureus. DESIGN AND SETTING:Systematic review with a search conducted in databases. METHODS:We conducted a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
0
10
2
1
Order By: Relevance
“…We found a high rate (44.2%) of methicillin resistance in our series. Nevertheless, in a recent review, Lima et al [21] reported an increase in antibiotic resistance among diabetic patients with foot infections and recommended the avoidance of wide empirical antibiotic coverage unnecessarily. Another important finding of this study was the fact that fusidic acid was efficient against all S. aureus species, including MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…We found a high rate (44.2%) of methicillin resistance in our series. Nevertheless, in a recent review, Lima et al [21] reported an increase in antibiotic resistance among diabetic patients with foot infections and recommended the avoidance of wide empirical antibiotic coverage unnecessarily. Another important finding of this study was the fact that fusidic acid was efficient against all S. aureus species, including MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…Wounds are a risk factor for colonization with methicillin-resistant S. aureus (MRSA) and other multidrug-resistant organisms, especially in hospital environments [14-18]. Bacterial colonization of wounds can increase wound severity and interfere with healing [6,11]. …”
Section: Introductionmentioning
confidence: 99%
“…in a hospital environment is therefore warranted, especially in wounds, which may be a source of cross-contamination by MRSA and coagulase-negative Staphylococcus spp. [11,15,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Three systematic reviews including four meta-analyses [24,35,57] and 10 systematic reviews without a meta-analysis [69,70,74,79,81,86,88,93,98,112] (Table 4 ; Additional files 4 and 6) examined healing improvements of diabetic foot/leg ulcers. Three had an AMSTAR score ≥8 [24,74,98].…”
Section: Resultsmentioning
confidence: 99%